THU0566 THE EFFECT OF KINESIO-TAPING ON CHRONIC NONSPECIFIC LOW BACK PAIN: PRELIMINARY RESULTS OF A DOUBLE BLINDED RANDOMIZED CLINICAL TRIAL. (2nd June 2020) - Aachari, I.; Samia, K.; Latifa, T.; Fatima Zahrae, T.; Afilal, S.; Safaa, F.; El Joumani, T.; Bahloul, S.; Rkain, H.; Hmamouchi, I.; Abouqal, R.; Allali, F.
Abstract : Background: The technique of Kinesio-Taping is a method of adhesive bandage exerting traction on the skin which would favorably influence the muscular and articular systems by reducing the pressure exerted on the subcutaneous mechanoreceptors thus reducing pain and muscle tension. Objectives: The aim of this study is to assess the effectiveness of Kinesio-Taping in the short and medium term on pain and function in patients with chronic nonspecific low back pain compared to a placebo. Methods: We conducted a double-blind, two-arm randomized clinical trial. The study should include a total of 70 patients randomized into 2 groups: Kinesio-Taping (n = 35) and control group (n = 35). To this date we have included 46 patients. All patients receives four I-shaped adhesive strips arranged in a star-like shape and applied to the most painful region of the lower back with a tension between 25% to 30% in the taping group. The placebo group received a taping procedure with no tension. Taping is applied three times (at baseline, fourth and eighth day). Patients are assessed at baseline, on day 14 and at 4 weeks by the Arabic version of the Oswestry Physical and Functional Disability Index (ODI) which is the primary outcome. The secondary outcomes are the assessment of pain and functional disability according to the visual analog scale (VAS) evaluated on a scale of 0 to 10, as well as Rolland-Morris score. Results: Both groups were comparable at baseline concerning the demographical and clinical characteristics (P > 0.05) (table 1 ). The result of repeated measures ANOVA showed a significant change in ODI score and in VAS for pain and functional disability as well as Rolland-Morris score in both groups. Using the ANCOVA, controlling for pre-test scores, a significant difference was found between the two groups (table 2 ). Table 1. Clinical characteristics of study population. Conclusion: Our clinical trial offers preliminary evidence on the superiority of Kinesio-Taping in the treatment chronic back pain compared to placebo concerning the reduction of pain and disability. Thus, it can be used as a complementary method in chronic non-specific low back pain. Table 2. Primary and secondary outcomes in the Kinesio-Taping and placebo group. Disclosure of Interests: None declared